KOMPARASI KISAH DEWI KĀLĪ MENGINJAK DADA DEWA ŚIVA DALAM SERIAL MAHAKALI PERSPEKTIF DEWI MĀHĀTMYAM - I Gusti Ngurah Agung Mahesa Mahaputra (UHN IGB Sugriwa Denpasar, 2022)
The common image of Goddess Kālī on the internet and Her worship in statues is that She is always depicted as stepping on Lord Śiva for some reason. The story of Goddess Kālī stepping on Lord Śiva's chest has a different narrative from what is shown in the Mahakali TV Series with Devī Māhātmyam (Mārkaṇḍeya Purāṇa), so it deserves to be studied under the title 'Reconstruction of the Story of Goddess Kālī Stepping on Śiva's Chest in Mahakali Series from Devī Māhātmyam's Perspective'. However, the description of the TV series about tattva behind Dewi Kālī stepping on Her husband is not supported by the stories of the Hindu Puranas and Tantras. The purpose of this study is to reintroduce the concept of the Godhead of Shaktism, especially the tattva of Goddess Kālī stepping on Her husband, Lord Śiva.